1994
DOI: 10.1111/j.1365-2249.1994.tb06030.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble intercellular adhesion molecule-1 (ICAM-1) in sera and bronchoalveolar lavage fluid of patients with idiopathic pulmonary fibrosis and pulmonary sarcoidosis

Abstract: SUMMARY ICAM‐1 plays an important role in inflammatory diseases. To assess level of soluble ICAM‐1 in the circulation and inflamed lesions, we measured levels of soluble ICAM‐1 in the circulation and bronchial veolar lavage fluid (BALF) of patients with idiopathic pulmonary fibrosis (IPF) and with pulmonary sarcoidosis (PS) and of healthy volunteers (HV), and we also analysed ICAM‐I expression of BALF cells in some patients and HV. IPF patients had significantly higher levels of circulating ICAM‐1 than HV, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 37 publications
0
6
0
3
Order By: Relevance
“…91 A follow-up study investigated the serum and BALF levels of ICAM-1 in IPF patients and again found significant elevations in the serum of IPF patients compared to both sarcoidosis patients and healthy volunteers, although BALF levels in IPF patients were not significantly elevated. 92 In another study of the serum levels of several ICAM proteins in IPF, the authors found both ICAM-1 and ICAM-2 to be significantly elevated in IPF patients and secondary ILD patients. The group then reviewed PFT results and found that while ICAM-2 was significantly inversely associated with DLCO levels, ICAM-1 levels were not significantly associated with any particular PFT.…”
Section: Intercellular Adhesion Molecule-1mentioning
confidence: 96%
“…91 A follow-up study investigated the serum and BALF levels of ICAM-1 in IPF patients and again found significant elevations in the serum of IPF patients compared to both sarcoidosis patients and healthy volunteers, although BALF levels in IPF patients were not significantly elevated. 92 In another study of the serum levels of several ICAM proteins in IPF, the authors found both ICAM-1 and ICAM-2 to be significantly elevated in IPF patients and secondary ILD patients. The group then reviewed PFT results and found that while ICAM-2 was significantly inversely associated with DLCO levels, ICAM-1 levels were not significantly associated with any particular PFT.…”
Section: Intercellular Adhesion Molecule-1mentioning
confidence: 96%
“…sICAM-1 has been detected in various body fluids including serum (Rothlein, Mainolfi et al 1991;Seth, Raymond et al 1991), cerebrospinal fluid (Tsukada, Matsuda et al 1993), synovial fluid (Mason, Kapahi et al 1993), sputum (Chihara, Yamamoto et al 1994), urine (Teppo, von Willebrand et al 2001) and bronchoalveolar fluid (Shijubo, Imai et al 1994). sICAM-1 is present in normal human serum at concentrations between 100-450 ng/ml (Gearing and Newman 1993), whilst elevated sICAM-1 has been found in serum from patients with cardiovascular disease, cancer, autoimmune disease and several studies have correlated serum levels of sICAM-1 with severity of disease (for review see (Witkowska and Borawska 2004)).…”
Section: Soluble Icam-1mentioning
confidence: 99%
“…ELISA for determination of sICAM-l in sera and BAL fiuids was performed according to a previously described method [8,14,21]. The FAST system (Becton Dickinson) was employed for quantitative analysis ofthe antigen.…”
Section: Elisa For Determination Ofsicam-i Concentrations In Sera Andmentioning
confidence: 99%